224k views
1 vote
Expand. Your answer should be a polynomial in standard form. (x2+4)(x2−6)=(x^2+4)(x^2-6)=(x2+4)(x2−6)=

User Mrsus
by
5.2k points

2 Answers

6 votes

Answer:

x⁴ - 2x² - 24

Explanation:

(x² + 4)(x² - 6)

x⁴ + 4x² - 6x² - 24

x⁴ - 2x² - 24

User PJx
by
5.2k points
3 votes

Answer:

x^4 -2x^2 -24

Explanation:

(x^2+4)(x^2−6)

FOIL

First: x^2*x^2 = x^4

Outer: x^2 *-6 = -6x^2

Inner: x^2 *4 = 4x^2

Last: 4*-6 = -24

Add them together

x^4 -6x^2 +4x^2 -24

Combine like terms

x^4 -2x^2 -24

This is in standard form since the powers decrease

User Brian Diggs
by
5.5k points